Land reclamation development under conditions of climate aridity growth: Experience of the Republic of Tatarstan - Khismatullin Mars; Khismatullin Marsel; Kurakova Chulpan; Khakimov Timur; Tazeev Emil (BIO Web of Conferences)
The paper investigates the issues of climate aridity growth and its impact on agronomic and economic efficiency of agricultural production in the Republic of Tatarstan. The role of complex land reclamation as one of the main directions of intensification of agriculture designed to mitigate the negative effects of drought, increase the fertility of arable land, prevent the spread of soil degradation and erosion and, of course, increase the efficiency of crop cultivation is studied. Analysis of agrometeorological observations for more than a century (1900-2021) has shown an increase in climate aridity in the region, especially in the last 40 years. The results of assessment of economic efficiency of irrigated farming in the republic show that in the existing natural and climatic conditions that 1.5% of arable land area under irrigation can produce up to 18% of crop production in Tatarstan. Underestimation of the role of land reclamation development in the agrarian policy of the state has been revealed, it should be developed at a faster pace to ensure food security of the country. On the basis of experimental studies on the basis of farms of different organisational and legal forms the high efficiency of land reclamation in combination with other innovative measures is proved. Based on the results of the research, appropriate recommendations have been developed to improve the effectiveness of state support measures, development of public-private partnership and introduction of science and technology achievements in land reclamation farming to prevent the impact of negative weather-climatic and anthropogenic factors on the economic efficiency of agricultural production and restrain the development of degradation of fertile land cover.